2016
DOI: 10.1108/apjml-05-2015-0077
|View full text |Cite
|
Sign up to set email alerts
|

Customer online shopping anxiety within the Unified Theory of Acceptance and Use Technology (UTAUT) framework

Abstract: Purpose Few studies have investigated how anxiety operates within the Unified Theory of Acceptance and Use of Technology (UTAUT) Framework. Consequently, this investigation explores the influence of anxiety on the customer adoption of online shopping based on the UTAUT. Design/methodology/approach The UTAUT's framework was extended by proposing new casual pathways between anxiety and its existing constructs (e.g. effort expectancy, perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
135
3
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 151 publications
(150 citation statements)
references
References 111 publications
(155 reference statements)
11
135
3
1
Order By: Relevance
“…Furthermore, Hill et al (1986) found that self-efficacy predicts intentions to use a wide range of technologically advanced products. Self-efficacy is considered as a personal judgment about the adequacy of knowledge, skill and willpower to accomplish an online shopping task (Celik, 2016). In a mobile shopping context, self-efficacy is consumers' judgment of their ability to use mobile shopping effectively (Compeau and Higgins, 1995).…”
Section: Tra-related Factors and The Intention To Adopt Mobile Shoppingmentioning
confidence: 99%
“…Furthermore, Hill et al (1986) found that self-efficacy predicts intentions to use a wide range of technologically advanced products. Self-efficacy is considered as a personal judgment about the adequacy of knowledge, skill and willpower to accomplish an online shopping task (Celik, 2016). In a mobile shopping context, self-efficacy is consumers' judgment of their ability to use mobile shopping effectively (Compeau and Higgins, 1995).…”
Section: Tra-related Factors and The Intention To Adopt Mobile Shoppingmentioning
confidence: 99%
“…Consequently, interesting findings have emerged from these studies. For example, some studies suggest that although consumers have positive attitudes towards various mobile activities such as mobile couponing, advertising, media, and social media, the majority does not possess positive attitudes towards M-shopping (Celik, 2016;Rao et al, 2011;Xu et al, 2009;Barutcu, 2008). Trust and personal innovativeness (PI) have been used broadly in a few studies, to extend TAM when studying consumer behaviours concerning mobile commerce such as mobile banking and payments, but have received less attention in M-shopping literature (Duane et al, 2014;Liébana-Cabanillas et al, 2014;Gu et al, 2009;Lee et al, 2012;Yang and Jolly, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…smartphones and tablets) and mobile technologies (e.g. 3G, 4G and 5G) has motivated mobile commerce (MC) to develop a global scope (Celik, 2016;Kalinic and Marinkovic, 2015;Lu, 2014). MC encompasses commercial transactions conducted via mobile apps or mobile versions of electronic commerce (EC) websites.…”
Section: Introductionmentioning
confidence: 99%